Dexamethasone protects against Aspergillus fumigatus-induced severe asthma via modulating pulmonary immunometabolism - Phyllis X.L. Gan; Wupeng Liao; Hui Fang Lim; W.S. Fred Wong (Elsevier, 2023)
Severe asthma is a difficult-to-treat chronic airway inflammatory disease requiring systemic corticosteroids to achieve asthma control. It has recently been shown that drugs targeting immunometabolism have elicited anti-inflammatory effects. The purpose of this study was to investigate potential immunometabolic modulatory actions of systemic dexamethasone (Dex) in an Aspergillus fumigatus (Af)-induced severe asthma model. Mice were repeatedly exposed to the Af aeroallergen before systemic treatment with Dex. Simultaneous measurements of airway inflammation, real-time glycolytic and oxidative phosphorylation (OXPHOS) activities, expression levels of key metabolic enzymes, and amounts of metabolites were studied in lung tissues, and in primary alveolar macrophages (AMs) and eosinophils. Dex markedly reduced Af-induced eosinophilic airway inflammation, which was coupled with an overall reduction in lung glycolysis, glutaminolysis, and fatty acid synthesis. The anti-inflammatory effects of Dex may stem from its immunometabolic actions by downregulating key metabolic enzymes including pyruvate dehydrogenase kinase, glutaminase, and fatty acid synthase. Substantial suppression of eosinophilic airway inflammation by Dex coincided with a specific escalation of mitochondrial proton leak in primary lung eosinophils. Besides, while our findings confirmed that inflammation corresponds with an upregulation of glycolysis, it was accompanied with an unexpectedly stable or elevated OXPHOS in the lungs and activated immune cells, respectively. Our findings reveal that the anti-inflammatory effects of Dex in severe asthma are associated with downregulation of pyruvate dehydrogenase kinase, glutaminase, and fatty acid synthase, and the augmentation of mitochondrial proton leak in lung eosinophils. These enzymes and biological processes may be valuable targets for therapeutic interventions against severe asthma.